Pigeon Towers of Iran - Morteza Farhadi (صفه, 1995)
In addition to the underground water canals which are among the most astonishing acheivements of mankind throughout the history of this planet, the pegion towers of Iran is the second and most important agricultural instalation in the previous decades.The pigeon towers whose exact area of domain is not yet recognized are truely unique in the world. One should truely consider their largeness, structural complexity and architectural beauty. These buildings which facilitate the production of the finest brand of natural fertilizers, although attracted the watchful eyes of western travellers who passed through or near the city of Isfahan; have miraculouslly remained a mystery to Iranian researchers even those who have specially wrote articles on the city of Isfahan, throughout the history.The pigeon towers are not only enourmouse in size, but also unique in regardes to their variety of forms. In the more developed examples is confronted with a space filled with the sound of music rather than anarchitectural space. In addition to the above mentioned characteristics, one should also note the application of different techniques and sciences (mathematics, geometry, physics, zoology and animal behavior)Today, the pigeon lowers of Iran, although highly regarded frog historical, economical, cultural and artistic                                are facing a speedy devastation for different sorts of reasons. The aim of thisarticle is to present a number of guidelines for their restoration and conservation.